External quality assessment for unfractionated heparin monitoring: An update from Australasia/Asia-Pacific - Favaloro, Emmanuel J.; Arunachalam, Sandya; Pasalic, Leonardo (Seminars in Thrombosis and Hemostasis)
UFH remains a major anticoagulant therapy applied within the acute hospital system. Due to patient variability, UFH monitoring is required to ensure patients remain free of thrombotic and bleeding complications. Monitoring of UFH therapy is usually achieved using either an APTT or an anti-factor Xa (anti-FXa) method. The former evaluates both the anti-factor IIa (anti-FIIa, or anti-thrombin) and anti-FXa anticoagulant activity of UFH and the latter evaluates just the anti-FXa anticoagulant activity of UFH. The APTT method is more widely utilised since APTT testing is performed by all hemostasis labs performing routine coagulation tests. However, the APTT method requires establishment of an APTT UFH therapeutic range. The anti-FXa method is favored in larger hospital sites and by most experts, and uses a standard UFH therapeutic range. We report findings for APTT and anti-FXa testing for UFH monitoring in our geographic region using recent data (past 5 years; 2020-2024 inclusive) from the RCPAQAP, an international EQA program, with over 110 enrolments for this EQA module. Four samples are assessed each year, with these comprising various levels of UFH. Good reproducibility was observed for duplicate samples sent in different surveys. CV (%) data revealed moderate variation for samples containing UFH (10-40% for anti-FXa; 10-25% for APTT). Anti-FXa reagents containing dextran sulphate tended to yield higher anti-FXa values than those without. Interpretations regarding UFH levels being below, within, or above therapeutic levels were generally reported as expected, according to the level of UFH present in the sample, especially for anti-FXa testing.